Validation of Confirmatory Factor Analysis (CFA) Adaptation of The Family Strengths Measurement Tool In Indonesian - Royhana, Safarina Firdausi; Jatnika, Ratna; Ariyanti Abidin, Fitri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The concept of family strength not only focuses on the ability to overcome challenges, but also involves identifying strengths that can be optimized within the family. Measurement instruments are needed to identify family strengths. One such measurement instrument is the Qatar Family Strength (QFS), which consists of seven dimensions: commitment to family, support for each other, effective communication, respect for each other, passing on family values and traditions, family resilience, and showing love and affection for each other. This study aimed to adapt and evaluate the psychometric properties of the Indonesian version of the Qatar Family Strength Scale (QFS). The QFS measures the extent to which family members believe that their family has strengths that make it a strong family. The instrument was piloted with 474 participants aged 15-18 years. The results showed that the Indonesian version of the QFS, with a seven-dimensional model (47 items), demonstrated good model fit (RMSEAWLSMV = 0.077, CFIWLSMV = 0.94, TLIWLSMV = 0.94). Additional validity tests, such as content validity index (CVI), and reliability tests using Cronbach's alpha were conducted. The findings show that the Indonesian version of the QFS with 47 items is reliable and valid.Konsep family strengths tidak hanya memfokuskan kemampuan dalam permasalahan yang dihadapi, melainkan terdapat pula identifikasi kekuatan yang dapat dioptimalkan dalam sebuah keluarga. Penggunaan alat ukur bertujuan untuk mengidentifikasi family strengths. Salah satu alat ukur family strengths adalah Qatari Family Strengths (QFS) yang terdiri atas tujuh aspek dimensi, yakni commitment to the family, support for each other, effective communication, respect for each other, conveying values and family traditions, family resilience, dan demonstrating love and affection for each other. Tujuan penelitian ini adalah untuk mengadaptasi dan menguji properti psikometri dari alat ukur Qatari Family Strengths (QFS) versi Bahasa Indonesia. QFS bertujuan untuk mengukur sejauh mana seorang anggota keluarga percaya bahwa keluarga mereka memiliki kekuatan yang menjadikan keluarga yang kuat (strong family). Alat ukur diujikan kepada 474 partisipan dengan status anak dengan rentang usia 15-18 tahun. Hasil menunjukkan bahwa alat ukur QFS versi Bahasa Indonesia dengan model tujuh aspek (47 item) memiliki model fit yang baik (RMSEAWLSMV=0.077, CFIWLSMV=0.94, TLIWLSMV=0.94). Uji validitas lainnya yang dilakukan adalah content validity index (CVI) serta untuk uji reliabilitas dilakukan dengan melihat nilai cronbach’s alpha. Hasil menunjukkan bahwa alat ukur QFS versi Bahasa Indonesia dengan 47 item termasuk dalam kategori reliabel dan valid.